Interpersonal Rejection, Ostracism, and Mentalisation in Women’s Friendships: Clinical Implications for Rumination - Deborah J. Oehlman Forbes (Psychotherapy and Counselling Journal of Australia)
Women’s friendships have long had cultural and psychological significance, particularly in the maintenance of positive social and emotional wellbeing. Inexplicable dissolution of these relationships correlates with a significant disruption of core human needs and mental health outcomes. Empirical research has found that ostracism, a variant of interpersonal rejection, is a distressing event since adult friendship attachment patterns are comparable to intimate partner relationships. In the field of mental health counselling and psychotherapy, theory can be an important precursor to intervention, but which theories and interventions may be suitable for post–friendship dissolution? Relational-cultural theory, a counselling and developmental framework, considers a broad range of psychological, social, healing connection, and relational experiences in the lives of women. Relational experiences starved of mutual empathic responses may evoke prolonged rumination in the friendship dissolution phase. In this regard, mentalisation-based treatment can help repair mental state affect such as prolonged rumination and restore emotion regulation. This is an unresearched topic that requires further investigation.